Unravelling the molecular basis of subcuticular host-colonization by the apple scab fungus, Venturia inaequalis : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy (PhD) in Plant Science, School of Agriculture and Environment, Massey University - Rocafort Ferrer, Mercedes (Massey University, 2023)
Scab, caused by the fungal pathogen V. inaequalis (Vi), is the most economically important apple disease. During infection, Vi occupies the subcuticular environment, where it develops specialized infection structures, called stromata and runner hyphae. These structures are thought to be important for fungal nutrition and the delivery of proteins, with many of these anticipated to function as virulence factors (effectors) in promoting host infection or avirulence factors (Avr effectors) in triggering host resistance. To date, nothing is known about how these structures are differentiated and protected from recognition by the host immune system. Likewise, little is known about the identity and function of Vi effector proteins. To better control scab, a greater understanding of the molecular mechanisms underpinning infection structure differentiation and protection, as well as Vi virulence and avirulence, is first needed. In Chapter 2, a comprehensive review of apoplastic effector proteins from plant-associated fungi (and oomycetes) was provided. Given that Vi is an extracellular pathogen, this review provided insights into the potential types of effector proteins secreted by Vi into the subcuticular environment. Then, in Chapter 3, a multidisciplinary approach based on bioinformatics, transcriptomics, and structural biology was used to identify and characterize Vi effector candidates (ECs). This revealed that ECs were predominantly expressed in two temporal waves, and that many belonged to expanded protein families with predicted structural similarity to virulence and avirulence effectors from other plant-pathogenic fungi. This analysis helped to generate a list of ECs for further study and contributed to a better understanding of effector biology and evolution. Next, in Chapter 4, a multidisciplinary approach based on transcriptomics, proteomics, glycomics, and confocal microscopy was used to study Vi cell wall carbohydrate composition during the differentiation of infection structures. This iii revealed that Vi down-regulates genes putatively associated with the biosynthesis of immunogenic carbohydrates, and deacetylates surface-exposed chitin to the less immunogenic carbohydrate, chitosan. Finally, in Chapter 5, CRISPR-Cas9 technology was applied to Vi for the first time, which will enable genes identified in this study to be functionally characterized. Altogether, this thesis has furthered our understanding of the Vi –apple pathosystem and has provided novel data that can be used to inform the development of new scab control strategies against Vi.
Figures 1-1, 1-2, 1-3, 1-4, 1-5, 1-7, 1-8 and 1-9 have been re-used with permission.
Listed in 2023 Dean's List of Exceptional Theses
Keywords: Venturia inaequalis; Apple scab; Apples; Diseases and pests; Control; Host-fungus relationships; Dean's List of Exceptional Theses; 300804 Horticultural crop protection (incl. pests, diseases and weeds)